1992
DOI: 10.1002/mrd.1080330107
|View full text |Cite
|
Sign up to set email alerts
|

Recovery of penetration ability in protease‐treated zona‐free mouse eggs occurs coincident with recovery of a cell surface 94 kD protein

Abstract: Previous studies have demonstrated that protease treatment of zona-free mouse eggs impairs sperm-egg interaction (Boldt et al.: Biol Reprod 39:19-27, 1988) and causes modification of a 94 kD egg plasma membrane protein (Boldt et al., Gamete Res 23:91-101, 1989). In this report, the ability of eggs to recover penetration ability following protease treatment was examined. Zona-free mouse eggs were isolated and treated with either trypsin or chymotrypsin (1 mg/ml, 20 min), then cultured for 0, 3, or 6 hr before i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

1993
1993
2006
2006

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 20 publications
1
21
0
Order By: Relevance
“…More recent studies seem to provide insight into the phenomenon from a molecular perspective. Cell-surface radiolabeling with 125I demonstrated that trypsin or chymotrypsin treatment was associated with loss or modification of a 94-kDa protein [14], and recovery of penetrating ability was coincident with recovery of the protein [15]. Although it is still unclear whether this protein molecule plays an integral role as a sperm receptor in sperm-egg fusion, the results seem to provide evidence that reconstruction of damaged surface molecules is needed for successful fertilization.…”
Section: Introductionmentioning
confidence: 70%
See 1 more Smart Citation
“…More recent studies seem to provide insight into the phenomenon from a molecular perspective. Cell-surface radiolabeling with 125I demonstrated that trypsin or chymotrypsin treatment was associated with loss or modification of a 94-kDa protein [14], and recovery of penetrating ability was coincident with recovery of the protein [15]. Although it is still unclear whether this protein molecule plays an integral role as a sperm receptor in sperm-egg fusion, the results seem to provide evidence that reconstruction of damaged surface molecules is needed for successful fertilization.…”
Section: Introductionmentioning
confidence: 70%
“…After 1 h preincubation of eggs, the fusion rate at 10 min was markedly improved. Kellom et al [15] suggested that a 94-kDa protein that was modified after protease treatment was not newly synthesized but was budding during egg preincubation. The molecule(s) damaged by acid treatment might be repaired in the same way, and it takes at least 2 h for eggs to be competent to fuse with sperm.…”
Section: Discussionmentioning
confidence: 99%
“…ZP removal methods significantly alter oolemmal proteins and may reduce fertilization (Santella et al, 1992;Kinn and Allen, 1981;Kellom et al, 1992), a mechanical technique for ZP removal was performed using a pair of microdissection scissors under a binocular microscope (Ji et al, 1998). This technique is particularly gentle as no recovery time is necessary before insemination (Ji et al, 1998).…”
Section: Resultsmentioning
confidence: 99%
“…In vitro matured metaphase II were obtained by incubating germinal vesicle or metaphase I stage oocytes under a 5% CO 2 atmosphere at 37°C for 24 hours. ZP was removed with a chemical-and enzymatic-free technique, using a pair of microdissection scissors under a binocular microscope, in order to preserve the integrity of the surface proteins (Kellom et al, 1992).…”
Section: Preparation Of Human Gametes and Fusion Assaysmentioning
confidence: 99%
“…Their effects on early mouse embryos have not been investigated extensively; however, studies on 8-cell embryos have shown that, at this stage, embryos are sensitive to low concentrations of monensin, and that BFA and monensin appear to have qualitatively different effects on the distribution of newly synthesised gap junction protein connexin 43, suggesting different modes of action (De Sousa et al, 1993). However, a complete block on oocyte surface turnover does not occur, since unfertilised oocytes can recover rapidly from proteolytic removal of a putative sperm-binding protein by a process independent of protein synthesis (Kellom et al, 1992). The precise nature of the Golgi apparatus in maturing or Mil mammalian oocytes is not clear.…”
Section: Discussionmentioning
confidence: 99%